Doubly electrically tuned cylindrical Bragg fiber waveguide inline optical filter for multiwavelength LASER applications - Chourasia N.K.; Srivastava A.; Kumar V.; Chourasia R.K. (My University, 2025)
In present communication, doubly tuned Bragg fiber waveguide low power inline optical filter with voltage tunable single crystal PMMA defect cavity is theoretically modeled and discussed using Henkel formalism in a cylindrical coordinate system for multiwavelength LASER applications. The structure provides photonic band gap (PBG) with a resonant transmission peak in the obtained PBG region. The defect cavity thickness is controlled by applying an external electric DC voltage. Initially, PBG of the proposed inline optical filter may tune-up to 828nm by modulating the incidence angle upto 80°. Thus, the resonant transmission peak also blue-shifted by 243nm, which can further tuned in presence of DC voltages and so-called doubly electrically tuned. Further, in doubly electrically tuned mode, the application range of such a device is very large up to 129nm for a small change in voltage range about 20V. Thus, the present device can be utilized as multiwavelength laser sources. © 2020 Elsevier Ltd